Representation Of Women's Beauty In Indonesia In Imperfect Film: Career, Love And Scales - Sazudda, Hanna Nur; Malik, Nugraha Abdul; Nurfalah, Farida; Wulandari, Sri (Journal of World Science, 2024)
This study examines the representation of beauty and physical appearance associated with the double standards faced by Indonesia women, as depicted in the film "Imperfect: Career, Love, and Scales". The reason for choosing this study is that researchers are interested in discussing the representation of beauty, especially women in Indonesia, as well so that researchers can make a valuable contribution in understanding the complex dynamics behind people's views on beauty and its implications in daily life. The purpose of this study is to examine the interpretation of Indonesia Women's Beauty in the narrative of the film and to produce knowledge that can be used in formal and informal education to increase awareness about the social and psychological implications of beauty representation. The methodology applied in this analysis is a qualitative approach, a qualitative approach is used to understand social phenomena in depth, from a complex and contextual point of view through semiotic analysis techniques based on the theory developed by Charles. Charles systematic theory of signs and their interpretation process helps to understand how meaning is constructed, transmitted, and interpreted in the context of human communication. The findings of this analysis show a number of scenes that critically raise the sensitive issue of the perception that women who are considered beautiful are often depicted with physical features such as thin bodies and fair skin. By acknowledging and celebrating this diversity, we can foster a more inclusive and appreciative understanding of different forms of beauty, while strengthening national cultural identity.